PENDAMPINGAN AI LITERACY: “PEMANFAATAN CHATGPT DAN TOOLS KECERDASAN BUATAN UNTUK PRODUKTIVITAS AKADEMIK MAHASISWA”: Pendampingan AI Literacy - Ananda, Armalia Reni Wijayanti; Surya, Andi; Surya, M. Renandi Ekatama; Yulistina; Nurahman, Dwi; Helmita, Helmita (WIDHARMA - Jurnal Pengabdian Widya Dharma, 2025)
Artificial intelligence (AI) has become a transformative tool in higher education, yet many students lack the skills to utilize it effectively. This community service program aims to enhance students' AI literacy through workshops on leveraging ChatGPT and other AI tools for academic productivity. Using hybrid training (offline and online), live demonstrations (ChatGPT, Gemini, Bing AI), and hands-on mentoring, the program involved 50 multidisciplinary students from University X. Post-workshop evaluation revealed a 75% improvement in participants' ability to use AI for academic writing, research, and time management. The initiative aligns with SDG 4 (Quality Education) and SDG 9 (Industry, Innovation, and Infrastructure).